Mitigating the Gap Between the Rich and the Poor: Key Trends and Drivers of Redistribution - Martin Larch; Philipp Mohl (Intereconomics, 2020)
The growing inequality of market income has attracted considerable attention; less so the redistribution of income. This article analyses key trends and drivers of income redistribution in the EU and the world. It shows that in the EU increasing redistribution has largely stabilised the dispersion of disposable income since the late 1990s. Only some advanced countries with a dominant free market ideology have recorded an increasing inequality of disposable income alongside a growing inequality of market outcomes. The evidence from panel data shows that the degree of redistribution increases with per capita income and with the share of low-tech, low-income sectors in manufacturing as well as, in line with the median voter model, when more than half of the voters earn less than the average income in countries with a majoritarian electoral system. More redistribution is associated with lower budgetary surpluses or higher deficits.
Keywords: 330